Antibacterial and antibiofilm activity of polyfunctional benzimidazole derivatives - Yu. V. Zaitseva; D. O. Egorov; R. S. Begunov; A. I. Khlopotinin (Acta Biomedica Scientifica)
Introduction. Compounds based on fused imidazole derivatives can become the basis for the development of a new generation of clinical therapeutic agents for more effective treatment of resistant human bacterial infections. This requires research, including the design, synthesis, and screening of biologically active compounds of this group.The aim. To study the effect of polyfunctional benzimidazole derivatives on the survival of Escherichia coli AB1157 culture and its ability to form biofilms.Methods. The antibacterial activity of the studied compounds was evaluated using the serial dilution method. Modeling of the formation of biofilms was carried out in the wells of an immunological plate with subsequent staining of the biomass with crystal violet.Results. The inhibitory activity of some of the studied compounds on the formation of biofilms by the Gram-negative bacterium E. coli AB1157 was demonstrated. The most pronounced inhibitory effect on E. coli AB1157 biofilms was exerted by 5-bromo-2-(trifluoromethyl)-1-H-benzimidazole. The level of biofilm formation decreased by 2–4 times in the area of concentrations of 15–60 µg/ml and by 8–10 times at concentrations of 125 µg/ml and above.Conclusion. The presented work expands the knowledge about the biological activity of benzimidazoles. The obtained results show that benzimidazole derivatives are good candidates for the development of new drugs against biofilms. The data obtained are of practical interest and need further study.